3-[(Z)-Benzylidene]-2,3-dihydro-1,5-benzothiazepin-4(5H)-one - Sabari, V. (International Union of Crystallography, 2011)
In the title compound, C(16)H(13)NOS, the seven-membered ring adopts a distorted half-chair conformation. In the crystal, molecules are linked by N—H⋯O hydrogen bonds, forming chains running along the b axis. The crystal packing is further stabilized by C—H⋯O interactions.